Broadband on‐chip contact pad to microstrip transition with low loss in SiGe BiCMOS technology. Issue 23 (1st November 2018) - von Vangerow, C.; Göttel, B.; Müller, D.; Zwick, T.
Abstract : A broadband, compact on‐chip contact pad to microstrip transition for use in silicon (Si) based technologies operating up to 330 GHz has been investigated and fabricated. The pad is designed as a short coplanar waveguide structure to concentrate the electrical field in the narrow gap between signal and ground pads, thus eliminating the need for a substrate shield while preserving low interaction with the lossy silicon substrate. The working principle is confirmed by electromagnetic field simulations using a detailed model of a high‐frequency measurement probe, which allows to investigate the field distribution with a realistic excitation source. The fabricated test structure with two transitions in a back‐to‐back configuration shows excellent broadband properties and insertion loss below 4.2 dB up to 330 GHz, making the proposed structure well suited for millimetre‐wave applications.